Hallux valgus among sales promotion women wearing high heels in a department store. (19th February 2019) - Soemarko, Dewi S; Rahmasari, Fita; Kamal, Achmad Fauzi; Cahayadi, Sigit Daru; Herqutanto,
Background: Wearing high heels for an extended period of time can cause several pathological conditions in women's feet, one of such is the hallux valgus (HV), as shown by a number of cross-sectional studies. This study aims to evaluate the incidence of HV among sales promotion women and to know the association of the high heel shoes with the severity of HV in that population. Method: This study used comparative cross-sectional design between two groups, wearing high heel and flat shoes; sales promotion women who work for at least 1 year were recruited as subjects by means of purposive sampling and were given questionnaires, and then physical and radiological examination of the foot were performed to detect any HV and its severity. Result: Incidence of HV is 25.25% (25 of 99) among subjects who were wearing high heel shoes and 10.87% (10 of 92) for those who were wearing flat shoes. Subjects wearing high heel shoes are 2.77 times (95% confidence interval (CI): 1.25–6.15; p = 0.01) more at risk for developing HV than those who wore flat shoes. The incidence of HV increases with age ( p < 0.05). Those who have been working for >4 years are 5.2 times (95% CI: 1.95–14.31) at more risk for developing HV than those who have been working for ≤4 years ( p < 0.001). The duration of wearing shoes per day, the type of toe box, and body mass index are not statistically significant with HV ( p > 0.05). The incidence of HV increased among overweight and obese subjects ( p > 0.05). The severity of HV in subjects was mostly mild to moderate. Conclusion: The incidence of HV is higher among sales promotion women who wear high heel shoes than flat shoes. Age and working experience are also related to the development of HV. Factors that affect the severity of HV cannot be shown in this study.